2013
DOI: 10.5811/westjem.2013.1.13347
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Foreign Bodies and Child Sexual Abuse: An Important Consideration

Abstract: Vaginal foreign bodies are a complaint occasionally encountered in pediatric clinics and emergency departments, and when pediatric patients present with a vaginal foreign body sexual abuse may not be considered. We describe two children with vaginal foreign bodies who were found to have been sexually abused. Each child had a discharge positive for a sexually transmitted infection despite no disclosure or allegation of abuse. We recommend that all pre-pubertal girls who present with a vaginal foreign body shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Closson FT et al suggested that child / sexual abuse should not be forgotten in case of a vaginal FB in prepubertal girl. [3] A variety of symptoms may be seen in case the event is unnoticed. Vulvo-vaginitis, vaginal bleeding, blood tinged / malodorous vaginal discharge, dysuria with lower abdominal pain, all may occur with a disc battery as with other long standing vaginal FBs.…”
Section: Discussionmentioning
confidence: 99%
“…Closson FT et al suggested that child / sexual abuse should not be forgotten in case of a vaginal FB in prepubertal girl. [3] A variety of symptoms may be seen in case the event is unnoticed. Vulvo-vaginitis, vaginal bleeding, blood tinged / malodorous vaginal discharge, dysuria with lower abdominal pain, all may occur with a disc battery as with other long standing vaginal FBs.…”
Section: Discussionmentioning
confidence: 99%
“…A brief communication has described that, in some communities, it is a common practice for girls to masturbate using aerosol canisters [7] . However, the presence of any vaginal foreign body in a prepubertal girl should elicit concern for sexual abuse, and testing for sexually transmitted infections should be included in the workup [8] .…”
Section: Discussionmentioning
confidence: 99%
“…At times, the object may be placed deep inside and may be missed on local examination or even a rectal examination [3]. There have been reports of vaginal foreign bodies which were eventually found to be cases of sexual abuse [4]. Therefore, one should always exclude the possibility of abuse in such cases when dealing with children who present with vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%